Education policies and optimal taxation (2008)
This paper studies the design of education policies in a setting in which optimal redistributive labor taxation is available. It is usually argued that the crucial parameter to guide education policy is the complementarity of education and ability. This is true only when labor supply is fixed or when income taxes are not allowed. I show that, if labor supply is endogenous and if the government can tax income in a nonlinear way, the crucial parameter is how the education elasticity of wage changes with ability. Taking the elasticity criterion into account, education subsidies are optimal in cases in which, under the complementarity criterion, education taxes would be optimal. To do this, I use an asymmetric information setting that motivates nonlinear taxation of income and education. © 2007 Springer Science+Business Media, LLC.